National systems of innovation - Acs, Zoltán J.; Audretsch, David B.; Lehmann, Erik E.; Licht, Georg (The Journal of technology transfer, 2017)
The perhaps broadest approach to economic performance at the level of a country is the concept of national systems of innovation. Despite the emergence of a compelling literature identifying the persistence of innovative activities and country specific institutional effects, evidence on the nature of national systems of innovation is still missing and a number of crucial questions and answers remain unanswered. To shed light on these issues, as of leading scholars of entrepreneurship and innovation was assembled from around the world for a conference on “National Systems of Entrepreneurship and Innovation” at the ZEW Mannheim in November 2014. This article draws on the NSI framework, sets it in a larger context, examines the logic of the approach and introduces the special issue by summarizing the papers presented at the conference and selected for this special issue.